2019
DOI: 10.4018/ijisp.2019010106
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Routing Protocol for Location Privacy Preserving in Internet of Things

Abstract: Internet of Things is a norm which has expanded very swiftly with high magnitude of heterogeneity and functionalities. Security and privacy became the prime factors of Internet of Things due to unsecured character of wireless communication. Thus, because of unsecured network, it is easy for invaders to trace and find the position of nodes during communication and leak the information. Issues related to location information may include sharing of information, storage, sensing, and processing which can be used b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…These factors provide a significant understanding for explaining the usage behavior of the stakeholders to use and adopt IoT in India. Though in different locations, Indians possess different cultural dispositions, but, in general, it is observed that the Indians are considerably influence by the societal pressure (Hofstead, 1997;Kaur et al, 2019). That is why the users' intention and subjectivity are found to be influenced by the societal habits and norms in the context of this study.…”
Section: Theoretical Backgroundmentioning
confidence: 62%
See 2 more Smart Citations
“…These factors provide a significant understanding for explaining the usage behavior of the stakeholders to use and adopt IoT in India. Though in different locations, Indians possess different cultural dispositions, but, in general, it is observed that the Indians are considerably influence by the societal pressure (Hofstead, 1997;Kaur et al, 2019). That is why the users' intention and subjectivity are found to be influenced by the societal habits and norms in the context of this study.…”
Section: Theoretical Backgroundmentioning
confidence: 62%
“…In this context, it is expected that when complete adoption of IoT technology will be there in India, people will realize its usefulness and would use the IoT enabled devices since it will help them a lot with minimum efforts (Seetharaman et al, 2019). Studies subscribed that once Indians would use this technology, they will start realize its effectiveness and other multifarious benefits (Kaur et al, 2019) and as a result, their attitude will be aligned to intend to use IoT enabled devices in a smarter way (Hussain et al, 2018). A survey was conducted in Spain by 31 experts to validate a IoT-based model and it was transpired that trust, usefulness, ease of use, compatibility were considered vital factors of the consumers of Spain to use IoT enabled devices (Joseph et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In an IoT environment, privacy must be a significant concern; for instance, privacy issues may arise in different phases of data sharing and interaction due to a large number of location information generation and collection in IoT devices. Location-based information in the IoT includes sensing, detecting, storing, processing, sharing, and using data among devices [8][9][10][11][12][13][14]. A GPS sensor gathers information of locations that could be very sensitive for few uses.…”
Section: Introductionmentioning
confidence: 99%